2017
DOI: 10.3892/mco.2017.1149
|View full text |Cite
|
Sign up to set email alerts
|

Role of RAS mutation status as a prognostic factor for patients with advanced colorectal cancer treated with first-line chemotherapy based on fluoropyrimidines and oxaliplatin, with or without bevavizumab: A retrospective analysis

Abstract: Abstract. The role of Kirsten rat sarcoma viral oncogene homolog (KRAS) and neuroblastoma RAS viral oncogene homolog (NRAS) mutations as negative predictors for anti-epidermal growth factor receptor (EGFR) therapies in metastatic colorectal cancer (CRC) has been firmly established. However, whether the RAS mutation status plays a role as a biomarker for anti-vascular endothelial growth factor (VEGF) treatment remains controversial. Data from 93 CRC patients who received first-line cytotoxic chemotherapy with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This study demonstrates that RAS and KRAS mutant status underline special clinicopathological and molecular features. As reported in some studies [15,28,29], in our context, RAS mutated CC was associated with female gender, distal colon, classical adenocarcinoma subtype, moderately differentiated tumors, and presence of vascular invasion. Interestingly, our study demonstrated that CC with RAS and epically KRAS mutations show a lower rate of the total lymph node.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study demonstrates that RAS and KRAS mutant status underline special clinicopathological and molecular features. As reported in some studies [15,28,29], in our context, RAS mutated CC was associated with female gender, distal colon, classical adenocarcinoma subtype, moderately differentiated tumors, and presence of vascular invasion. Interestingly, our study demonstrated that CC with RAS and epically KRAS mutations show a lower rate of the total lymph node.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, our study demonstrated that CC with RAS and epically KRAS mutations show a lower rate of the total lymph node. Recently, NOGUERA et al [29] found the same observation, but the difference was not statistically significant. Besides, patients with KRAS mutations showed a significantly higher rate of positive lymph nodes.…”
Section: Discussionmentioning
confidence: 71%
“…Even if these differences did not reach the statistically significant level, probably due to the relatively small effect of RAS mutations and the rarity of BRAF mutations, RAS/PIK3CA/BRAF status appeared to be a promising candidate to help in identifying tumors that will respond to the anti-VEGF drug [ 13 ]. Another work was not able to found an association between RAS mutational status and BV efficacy; however, this investigation was performed on small study population and only a subgroup of patients ( n = 35) was treated with BV-containing regimes [ 14 ]. Interestingly, a recent pioneering study on 167 patients who underwent lung metastasectomy for mCRC, has reported for the first-time that for patients with KRAS codon 12 mutations, perioperative bevacizumab was associated with a significant improvement in both loco-regional recurrence free survival and OS [ 15 ].…”
Section: Pharmacogenomics Of Approved Molecules Targeting the Vegfmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) - targeted monoclonal antibodies (MAb), such as cetuximab and panitumumab, have been used in the treatment of metastatic colorectal cancer (mCRC) since 2004. Numerous studies have demonstrated that RAS mutations are associated with resistance to anti-EGFR antibodies and that approximately 45–50% of CRCs harbor a RAS mutation [ 4 , 5 ]. Based on these findings, anti-EGFR MAbs have been recommended for use in first-line therapy of metastatic CRC (mCRC) for those patients whose tumors are wild-type (WT) for RAS.…”
Section: Introductionmentioning
confidence: 99%